Circuits of Knowledge and Techniques: The Transnational Flow of Planning Ideas and Practices. (2nd July 2013) - Healey, Patsy
Abstract This article considers the conceptual and methodological tools which may help to focus the critical analysis of transnational flows of planning ideas and practices in the present period. The discussion starts from the rejection of the 'modernization myth' with its linear concept of a single development trajectory and reviews the philosophical background to the array of alternative conceptions which have displaced it. It then examines three, often overlapping, fields of intellectual development which offer promising concepts for exploring contemporary transnational flows of planning ideas and practices: actor‐network theory (especially with respect to the way ideas and technologies get to 'travel' and get 'translated'), institutionalist versions of policy 'discourse analysis' (discourse structuration and institutionalization, in particular), and discussions about circuits of knowledge and hegemonic projects in the globalization and international development literatures. Drawing on these, I suggest that critical analysis of such flows should give special attention to the 'origin stories' of such ideas, their 'travelling histories' and the 'translation experiences' through which exogenous planning ideas and practices become 'localized'. I conclude by commenting on what may be distinctive about transnational flows in the present period, why undertaking critical analysis of such flows is valuable, and key methodological attitudes to keep in mind in conducting such analyses.